Penyediaan Tempat Cuci Tangan Dan Pembagian Masker Sebagai Upaya Pencegahan Covid-19 di Pura Giri Natha Puncak Sari Kabupaten Bintan - Luh Pitriyanti; Mutia Diansafitri (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2021)
Giri Natha Puncak Sari Temple is one of the Hindu temples located in the Archipelago Province. The purpose of this community service activity is to provide handwashing facilities and distribution of masks at Giri Natha Puncak Sari Temple, Bintan Regency to improve handwashing behavior in the community and preventive measures COVID-19. This method of community service is carried out by increasing knowledge through installing banners adapting new habits at places of worship and increasing understanding of the importance of handwashing and the use of masks, as well as making handwashing facilities during the COVID-19 pandemic. The making of handwashing facilities is directly carried out by the community in cooperation. The activities of making handwashing facilities, installing banners, and distributing masks received good responses from the community as an effort to prevent the spread of COVID-19 in the temple.